A robust framework for topological relations in the on-the-fly web map generalisation process. (2017) - Lejdel, Brahim; Kazar, Okba
With the technological development in the web, great numbers of users want access to spatial data on the web that is specific to their needs. This may be possible by applying the suitable generalisation process which consists to simplify the objects of the map and may transform the topological relations between them into another ones in real-time. This process called on-the-fly generalisation maps. Many approaches were proposed for improving this process, but those do not suffice to guide a powerful and efficient process. In this paper, we will propose a robust framework to transform the topological relationships during the on-the-fly web map generalisation and treat the problem associated to modelling of streets and rivers as linear objects because, in the reality (ground), they have some widths or areas. By considering a road or a river as a line or as an area, topological relationships can be different. We use mainly two types of object; ribbon and regions.